Role of chronic neuroinflammation in neuroplasticity and cognitive function: A hypothesis. Issue 11 (2nd March 2022) - Lecca, Daniela; Jung, Yoo Jin; Scerba, Michael T.; Hwang, Inho; Kim, Yu Kyung; Kim, Sun; Modrow, Sydney; Tweedie, David; Hsueh, Shih‐Chang; Liu, Dong; Luo, Weiming; Glotfelty, Elliot; et al.
Abstract: Objective: Evaluating the efficacy of 3, 6'‐dithioPomalidomide in 5xFAD Alzheimer's disease (AD) mice to test the hypothesis that neuroinflammation is directly involved in the development of synaptic/neuronal loss and cognitive decline. Background: Amyloid‐β (Aβ) or tau‐focused clinical trials have proved unsuccessful in mitigating AD‐associated cognitive impairment. Identification of new drug targets is needed. Neuroinflammation is a therapeutic target in neurodegenerative disorders, and TNF‐α a pivotal neuroinflammatory driver. New hypothesis: AD‐associated chronic neuroinflammation directly drives progressive synaptic/neuronal loss and cognitive decline. Pharmacologically mitigating microglial/astrocyte activation without altering Aβ generation will define the role of neuroinflammation in AD progression. Major challenges: Difficulty of TNF‐α‐lowering compounds reaching brain, and identification of a therapeutic‐time window to preserve the beneficial role of neuroinflammatory processes. Linkage to other major theories: Microglia/astroglia are heavily implicated in maintenance of synaptic plasticity/function in healthy brain and are disrupted by Aβ. Mitigation of chronic gliosis can restore synaptic homeostasis/cognitive function.